A state of secrecy Stasi informers and the culture of surveillance - Lewis, Alison, 1958- (Lincoln : Potomac Books, an imprint of the University of Nebraska Press, 2021)
A series of five interlaced, in-depth biographical studies from across the spectrum of writers-turned-spies recruited by the Stasi.
Cover -- Title Page -- Copyright Page -- Contents -- List of Illustrations -- Acknowledgments -- Introduction -- List of Abbreviations -- 1. Recruiting Writers for the Stasi, 1949-1962 -- 2. Handling Informants and Sustaining Motivation, 1962-1972 -- 3. Policing the "Line on Writers" and Living the Secret Life, 1971-1976 -- 4. The Secret War on Political-Ideological Diversion, 1976-1978 -- 5. Simulation and Secret Policing the Underground, 1979-1982 -- 6. The Culture Wars, 1983-1989 -- Conclusion -- Notes -- Selected Bibliography -- Index
Includes bibliographical references and index.
JSTOR
Keywords: Germany (East). -- Ministerium für Staatssicherheit -- History; Germany (East). -- Ministerium für Staatssicherheit; Informers -- Germany (East); Authors as spies -- Germany (East); Intelligence service -- Germany (East) -- History; Service des renseignements -- Allemagne (Est) -- Histoire; Intelligence service; Informers; Authors as spies; Germany (East); History